Peningkatan Kinerja Pegawai Pada Bagian Pelaporan Administrasi Keuangan Pada Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Agam - Desmayanti, Tety; Ariany, Ria (CV. ITTC INDONESIA, 2024)
This research aims to improve employee performance in the Financial Administration Reporting Section (Public Works and Spatial Planning Department of Agam Regency). The employee placement system at the Agam Regency Public Works and Spatial Planning Service is based on competency, education, training, and skills. The research was conducted using qualitative methods with a sample of informants consisting of revenue treasurers, computer operators, financial treasurers, and financial staff at the public works and spatial planning departments of Agam Regency. This research uses interview analysis techniques with stages, namely data reduction, data presentation, and conclusion drawing. The research results show that the third indicator used is education and training. Competency and skills have not become a priority. Then, related to the process of achieving employee work targets at the Public Works and Spatial Planning Department of Agam Regency, it is influenced by three main factors, namely employee ability, work motivation, and rewards. The most basic issue is the ability of employees. Whereas there are many programs carried out by the Public Works and Spatial Planning Department of Agam Regency in order to stimulate employees and encourage their performance, employee limitations are the main obstacle. Work motivation activities range from leadership roles to providing rewards for employees who have achieved significant contributions.